2020
DOI: 10.1371/journal.pone.0239318
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30-day mortality using point-of-care testing; an external validation and derivation study

Abstract: Background Early risk stratification for guiding treatment priority in the emergency department (ED) is becoming increasingly important. Existing prediction models typically use demographics, vital signs and laboratory parameters. Laboratory-based models require blood testing, which may cause substantial delay. However, these delays can be prevented by the use of point-of-care testing (POCT), where results are readily available. We aimed to externally validate a laboratory-based model for mortality and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…
Mortality rates are used to evaluate the quality of hospital care after adjusting for disease severity, age, comorbidity, and laboratory data that include complete blood counts (CBC). Previous studies have focused on selected CBC parameters only and have variously found that white blood counts (WBC), [1][2][3][4][5] proportion of neutrophils, 4 red cell counts (RBC), 3,4 red cell distribution widths (RDW), [6][7][8][9][10][11][12][13] mean corpuscular hemoglobin concentrations (MCHC), 1 platelet counts, 1,2,14 mean platelet volumes (MPV), 1,5,6 and neutrophil-lymphocyte ratios (NLR) 3,5,8,15,16 predict short-term mortality. We know of no attempts to identify the predictive value of all CBC parameters, with and without those provided by some modern analyzers, such as the proportion of large unstained cells (LUC), hypochromic cells, and macrocytes.
…”
mentioning
confidence: 99%
“…
Mortality rates are used to evaluate the quality of hospital care after adjusting for disease severity, age, comorbidity, and laboratory data that include complete blood counts (CBC). Previous studies have focused on selected CBC parameters only and have variously found that white blood counts (WBC), [1][2][3][4][5] proportion of neutrophils, 4 red cell counts (RBC), 3,4 red cell distribution widths (RDW), [6][7][8][9][10][11][12][13] mean corpuscular hemoglobin concentrations (MCHC), 1 platelet counts, 1,2,14 mean platelet volumes (MPV), 1,5,6 and neutrophil-lymphocyte ratios (NLR) 3,5,8,15,16 predict short-term mortality. We know of no attempts to identify the predictive value of all CBC parameters, with and without those provided by some modern analyzers, such as the proportion of large unstained cells (LUC), hypochromic cells, and macrocytes.
…”
mentioning
confidence: 99%